Integrated Social-Economic-Ecological Modeling for Fisheries: The ECOST Model - Failler, Pierre; Pan, Haoran; Akbari, Negar (Frontiers in Marine Science, 2022)
Marine and coastal areas are complex systems formed by the interaction among the local population, economy, environment and resources and there is an increasing tendency for recent studies in fisheries research to incorporate interdisciplinary methods in their approach. In this paper, the Integrated Social-Economic-Ecological model for Fisheries (ECOST) model is structured with three modules each of which intends to characterize some relevant aspects of social, economic and ecological systems, respectively. At the heart of the model stands a fisheries economic module describing the fisheries economy; within the model the economic module is extended to the areas of fisheries sociology and biology or ecology where social and ecological aspects of fisheries are modeled following appropriate theory and methodology, respectively.